1998
DOI: 10.3141/1647-15
|View full text |Cite
|
Sign up to set email alerts
|

Model of the Performance of a Roadway Safety Fence and Its Use for Design

Abstract: The optimization of roadway safety design by experimental means is expensive and time consuming. Computer simulation of such complex engineering systems improves understanding of how and why the system behaves as it does, aids in decision making, and reduces development costs and time involved. The simulation presented is based on a computer model developed from a study of the results of full-scale experiments of impact on the Brifen wire-rope safety fence (WRSF). The code comprises a dynamic vehicle model and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Using hierarchical tree regression method, Matthew et al quantified the impact of road characteristics on accident rates, research result showed that the road line shape and road conditions are the most important factors in traffic accidents [3]. Other run-off-roadway accident studies have examined particular roadside features such as roadway guardrail systems, utility poles, bridges, sign supports, side slopes and ditches and fences and their effect on the frequency and severity of accidents [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Using hierarchical tree regression method, Matthew et al quantified the impact of road characteristics on accident rates, research result showed that the road line shape and road conditions are the most important factors in traffic accidents [3]. Other run-off-roadway accident studies have examined particular roadside features such as roadway guardrail systems, utility poles, bridges, sign supports, side slopes and ditches and fences and their effect on the frequency and severity of accidents [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The comparisons made cover much more detail than the first study and provide substantial evidence for validating the individual models used within the simulation. An outline of the early development of the work, including some design implications, are presented in a conference paper published by the Transportation Research Board of America [4].…”
Section: Introductionmentioning
confidence: 99%